A Survey of Mining Association Rule Techniques - Sumitha, M; Suganya, P.S (International Journal of Computer Sciences and Engineering, 2025)
Association rule is a data mining techniques which is used to mine several algorithms of applying association rules from the given databases. One of the most important algorithm is Apriori that is used to extract frequent itemsets from large database and association rules are help to discovering the knowledge. Association rules are if/then statements that help uncover relationships between unrelated data in a relational database or other information repository. In this paper we mention different techniques for mining association rules from relational databases and their usage in different areas